Effect of pain neurophysiology education on physiotherapy students' understanding of chronic pain, clinical recommendations and attitudes towards people with chronic pain: a randomised controlled trial. Issue 4 (December 2017) - Colleary, G.; O'Sullivan, K.; Griffin, D.; Ryan, C.G.; Martin, D.J.
Abstract: Objective: To investigate the effect of pain neurophysiology education (PNE) on student physiotherapists': (1) knowledge of chronic pain; (2) attitudes towards patients with chronic pain; and (3) clinical recommendations for patients with chronic pain. Design: Multicentre single-blind randomised controlled trial. Setting: One UK and one Irish university. Participants: Seventy-two student physiotherapists. Intervention: Participants received either PNE (intervention) or a control education. Both were delivered in a 70-minute group lecture. Main outcome measures: (1) The Revised Pain Neurophysiology Quiz to assess knowledge; (2) the Health Care Pain Attitudes and Impairment Relationship Scale (HC-PAIRS) to assess attitudes; and (3) a case vignette to assess the appropriateness of clinical recommendations. Results: Post education, the PNE group had a greater increase in pain neurophysiology knowledge [mean difference 4.0 (95% confidence interval 3.2 to 4.7), P <  0.01] and more improved attitudes [−17.5 (95% confidence interval −22.1 to −12.9), P <  0.01] compared with the control group. Post education, students in the PNE group were more likely to make appropriate recommendations regarding work (94% vs 56%), exercise (92% vs 56%), activity (94% vs 67%) and bed rest (69% vs 33%) compared with those in the control group ( P  < 0.05). Conclusion: The improvements in knowledge, attitudes and recommendations for pain management show that PNE is a potentially valuable part of the education of physiotherapy students, and could be used on a more widespread basis. There is a need to investigate whether these findings can be replicated in other healthcare professions, and how well these reported changes lead to changes in actual clinical behaviour and the clinical outcomes of patients.